Human error prevention: using the human error template to analyze errors in a large transport aircraft for human factors considerations - Li, Wen-Chin; Harris, Don; Stanton, Neville A.; Hsu, Yueh-Ling; Chang, Danny; Wang, Thomas; Young, Hong-Tsu (Cranfield University, 2009)
Flight crews make positive contributions to the safety of aviation operations. Pilots have to assess continuously changing situations, evaluate potential risks and make quick decisions. However, even well trained and experienced pilots make errors. Accident investigations have identified that pilots’ performance is influenced significantly by the design of the flight deck interface. This research applies Hierarchical Task Analysis (HTA) and utilizes the - Human Error Template (HET) taxonomy - to collect error data from pilots during flight operations when performing a go-around in a large commercial transport aircraft. HET was originally developed in response to a requirement for formal methods to assess compliance with the new human factors certification rule for large civil aircraft introduced to reduce the incidence of design-induced error on the flight deck (EASA Certification Specification 25.1302). The HET taxonomy was applied to each bottom level task step in an HTA of the flight task in question. A total of 67 pilots participated in this research including 12 instructor pilots, 18 ground training instructor, and 37 pilots. Initial results found that participants identified 17 operational steps with between two and eight different operational errors being identified in each step by answering to the questions based either on his/her own experience or their knowledge of the same mistakes made previously by others. Sixty-five different errors were identified. The data gathered from this research will help to improve safety when performing a go-around by identifying potential errors on a step-by-step basis and allowing early remedial actions in procedures and crew coordination to be made.
Keywords: Aviation Safety, Human Errors, Hierarchical Task Analysis, Human Error Template